An investigation of the survival and/or growth of Clostridioides (Clostridium) difficile in beef stored under aerobic, anaerobic and commercial vacuum packaging conditions at 2 °C and 20 °C. (January 2021) - McSharry, Siobhán; Koolman, Leonard; Whyte, Paul; Bolton, Declan
Abstract: Although primarily considered to be a nosocomial infection, there is mounting evidence that food, including beef products, may be a source of Clostridioides ( Clostridium ) difficile . The objective of this study was to investigate the behaviour of this pathogen under atmospheric and temperature conditions that may be encountered in vacuum packaged retail beef. Inoculated steaks were stored in air, in low (950 cm 3 /m 2 ·d· bar), medium (<47 cm 3 /m 2 ·d· bar) and high barrier (<3 cm 3 /m 2 ·d· bar) vacuum packs and under anaerobic conditions at 2 °C and 20 °C. At 2 °C a steady decline in C. difficile concentrations was observed over the 32 days of storage, regardless of oxygen conditions. In contrast, in the temperature abuse scenario, the bacterial counts were significantly ( P < 0.05) higher in the medium and high barrier packs and under anaerobic conditions after 2 days and increased up to approximately 5 log10  cfu/g by day 8. It was concluded that under chilled conditions, C. difficile will survive, all-be-it at lower concentrations, for extended periods (up to 32 days) but in a temperature abuse scenario these bacteria will grow on beef steaks stored in medium and high barrier vacuum packs and under anaerobic conditions. Given the increase in community acquired C. difficile infections, the potential role of vacuum packaged steaks as a foodborne source of these pathogens requires further investigation. Highlights: C. difficile survives in vacuum packaged steaks at chilled temperatures. C. difficile will grow on medium and high barrier vacuum packaged steaks at abuse temperatures. Vacuum packaged steaks are a potential foodborne source of C. difficile.